Studies on Optimization of Growth Parameters for L-Asparaginase Production by Streptomyces ginsengisoli - Neelima Deshpande; Prachi Choubey; Manasi Agashe (The Scientific World Journal)
A species of Streptomyces, Streptomyces ginsengisoli, a river isolate, was evaluated for production of an enzyme, L-asparaginase, with multiple functions mainly anticancer activity. The actinomycete was subjected to submerged fermentation by “shake flask” method. The quantity of L-asparaginase produced was estimated as 3.23 μmol/mL/min. The effect of various culture conditions on L-asparaginase production was studied by adopting a method of variation in one factor at a time. Of the various conditions tested, glucose (followed by starch) and peptone served as good carbon and nitrogen sources, respectively, for maximal production of enzyme at pH 8. The temperature of 30°C and an incubation period of 5 days with 0.05 g% asparagine concentration were found to be optimum for L-asparaginase production.